Editor’s choice: recent research highlights from the International Journal of Nanomedicine - Shiekh FA (Dove Medical Press, 2017)
Farooq A Shiekh,1 Abdul-Rahman M Abu-Izzah,2 Vivian J Lee,2 Syed Mudassar1 1Department of Clinical Biochemistry, Sher-I-Kashmir Institute of Medical Sciences (SKIMS), Srinagar, India; 2Department of Basic Medical Sciences, Avalon University School of Medicine, Curacao, the NetherlandsIs nanomedicine really less harmful?Evaluation of: Thakkar A, Chenreddy S, Thio A, Khamas W, Wang J, Prabhu S. Preclinical systemic toxicity evaluation of chitosan-solid lipid nanoparticle-encapsulated aspirin and curcumin in combination with free sulforaphane in BALB/c mice. Int J Nanomedicine. 2016;11:3265–3276.Nanomedicine1 has increasingly received a tremendous attention over the past two decades as a potential multidimensional field, developing nano-applications that are transforming a host of medical products and services,2,3 including drug delivery4 and health-monitoring devices, and the possibility of gaining new insights about “undruggable targets” and treatment through atomic-scale precision is increasing rapidly.5 Although it is uncertain as to which of the new delivery platforms will become the most effective and useful, it is certain that many new approaches will be investigated in the years to come.4,6